Antecedents and consequences of service improvisation in the restaurant context - Oh, Hyunghwa (Kansas State University, 2019)
Service improvisation refers to how service employees deviate from standard manuals to respond immediately to unpredictable situations by using available resources. Service employees often confront unexpected requests and behaviors from customers. Thus, the ability to effectively and quickly respond to these requests can increase customer satisfaction and create a significant competitive advantage for a restaurant. Service improvisation may be important, but research is scarce in the hospitality literature. The purpose of this study was to determine not only antecedents of service improvisation, but also test a double-edged sword effect of service improvisation by proposing a moderator mitigating negative aspects of service improvisation. A total of 1,148 responses from frontline restaurant employees currently working in non-managerial positions in the U.S. restaurant industry were recruited from Amazon Mechanical Turk, an online survey platform. Previously validated measurement items were carefully selected for the online survey using a thorough literature review. Pre-screening questions and attention check questions were included to improve data quality. Confirmatory factor analysis confirmed reliability and validity of all the scale items. Then, hierarchical multiple regression analysis was used to test hypothesized paths. Direct relationships among three antecedents and service improvisation were confirmed: servant leadership (β = 0.106, p < 0.001), team-member exchange (β = 0.635, p < 0.001), and internal locus of control (β = 0.184, p < 0.001). Psychological empowerment was identified as a partial mediator between servant leadership and service improvisation (β = 0.802, CI [0.691, 0.912]), team-member exchange and service improvisation (β = 0.156, CI [0.108, 0.208]), and internal locus of control and service improvisation (β = 0.216, CI [0.137, 0.298]). As for the consequences of service improvisation, although service improvisation improved service recovery performance (β = 0.296, p < 0.001), the level of emotional exhaustion (β = 0.288, p < 0.001) also increased concurrently, which, in turn, decreases service recovery performance (β = -0.101, p < 0.01). Support for creativity moderates the link between service improvisation and emotional exhaustion (β = -0.121, p < 0.001). The contributions of the study to theory and practice are discussed along with limitations and recommendations for future research.
Keywords: Service improvisation; Servant leadership; Team-member exchange; Psychological empowerment; Service recovery performance; Restaurant frontline employee